The Supervisory Relationship: A Conceptual and Psychometric Review of Measures. (September 2016) - Tangen, Jodi L.; Borders, DiAnne
Abstract : To date, a comprehensive review of supervisory relationship measures has yet to be published. In this article, the authors explore conceptualizations of the supervisory relationship, describe and critique 11 measures, provide recommendations for researchers and practitioners when selecting measures, and offer suggestions regarding future measure development.